IMPLEMENTASI PROGRAM KOMPUTASI ALGORITMA KESEIMBANGAN LINTASAN PERAKITAN - Opit, Prudensy F.; Kornelis, Marsella T.; Mahardini, Karunia A. (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
Assembly line balancing problem (ALBP) is well known to perform an optimize line balance efficiency as a result of assigning a series of work elements under certain restrictions. Work elements, cycle time, process time for each work element, and number of predecessors are some of important inputs needed to generate the problem. In a real system, these data can always be changed. In some case, these data can also be extensive. Manual computation is not recommended to solve the problem. In addition to the length of time required, manual computation is often inaccurate. This paper implements special computing programs to solve simple line balancing problem (SLBP) faster and more accurate. Three common used of line balancing algorithms such as Computer Method for Sequencing Operations for Assembly Lines (COMSOAL), task with Least Number of Predecessors (TLNP), and Largest Candidate (LC) are programmed using three different tools, VBA Excel 2007, Visual Basic (VB) database 6.0, and Visual Studio 2008 C++. The programs will be able to read a maximum of 50 work elements and a maximum of 5 predecessors for each work element inputted by users. The results will be the optimum number of work stations, work elements assigned for each station, and line balance efficiency.